Reflection of the "Law of unity and struggle of opposites" in the dialectic of Jalаliddin Rumi - Sayfulloevna, Ashurova Marhabo (International Journal of Psychosocial Rehabilitation, 2020)
This article, based on the "Law of Unity and Struggle," analyzes the basis of the dialectic of Jalaliddin Rumi and other aspects of dialectics through the concept of "conflict." Based on the article, a comparative analysis of the Rumi dialectics with Western dialectics is taken. These conclusions are analyzed in parallel with modern philosophical dialectics. The article is important for covering the interaction of different comments in Western and Eastern philosophy. The main conclusions in this article are that in philosophy, in the views of Rumi, the dialectic of the connection between the spirit and the mind of man is obvious.